The poverty of (critical) theory: a review - Strumska-Cylwik, Longina (Acta Academica: Critical views on society, culture and politics, 2019)
The subject of this review is the paper by Bert Olivier titled “The poverty of (critical) theory”, a work to which one cannot remain indifferent. It provokes one into discussion, touches one’s conscience, fills one with bitter reflection on the condition of critical theory and the condition of humanity and the modern world, and at the same time it induces fear for their future fate.